Bichannel design inspired by membrane pump: a rate booster for the conversion-type anode of sodium-ion battery. Issue 7 (24th January 2022) - Yin, Bo; He, Haiyong; Lin, Jiande; Hong, Youran; Cheng, Boshi; Zhu, Lin; He, Hualong; Ma, Mingchan; Wang, Jiangwei
Abstract : The hierarchical carbon, i.e. the internal carbon network and external carbon shell, as the transport pathway of electrons and pyrophosphate as a conductor of Na + are integrated to promote the sodium storage performance of the conversion-type anode. Abstract : The sluggish kinetics of Na + in anode limits the rate capability of sodium-ion batteries (SIBs). Herein, pyrophosphate, as a Na + pump in the cell membrane, is integrated with cobalt redox-active center to obtain a new type of anode material for SIBs with a high Na + diffusion rate. After combining with the hierarchical carbon network, bichannel structure is formed to accelerate the transport of electrons and ions, where the carbon network serves as the transport channel for electrons and pyrophosphate for Na + . High conductivity of electrons and ions results in the high pseudocapacitance ratio of CPOC@C-700 (95% at 1 mV s −1 ), indicating a high rate capability (190.3 mA h g −1 at 5 A g −1 ). A series of ex situ characterizations demonstrate the high reversibility of the redox center and stability of the bichannel structure during cycling. Consequently, CPOC@C-700 maintains 71.1% of the capacity after 1000 cycles at 2 A g −1 . This bichannel design concept is anticipated to promote further applications of SIBs.